Electromagnetic Fields on Time-Involute Particles Around Biharmonic Particles and its Lorentz Transformations in Heisenberg Spacetime - Körpınar, Talat; Asıl, Vedat; Turhan, E. (Springer New York LLC, 2014)
In this paper, we obtain the new parametric representation for a time-involute particles in Heisenberg spacetime (Formula presented.) (Formula presented.) (Formula presented.)(Formula presented.). Moreover, we obtain Lorentz transformations this particles. Finally, we give the relationship of electromagnetic fields on Heisenberg spacetime. © 2014, Springer Science+Business Media New York.
Keywords: Bienergy; Energy; Faraday tensor; Heisenberg group; Involute particle; Lorentz transformations